MobiDB 3.0: more annotations for intrinsic disorder, conformational diversity and interactions in proteins. Issue Volume 46:Issue D1(2018) (10th November 2017) - Piovesan, Damiano; Tabaro, Francesco; Paladin, Lisanna; Necci, Marco; Mičetić, Ivan; Camilloni, Carlo; Davey, Norman; Dosztányi, Zsuzsanna; Mészáros, Bálint; Monzon, Alexander M; Parisi, Gustavo; Schad, Eva; et al.
Abstract: The MobiDB (URL: mobidb.bio.unipd.it) database of protein disorder and mobility annotations has been significantly updated and upgraded since its last major renewal in 2014. Several curated datasets for intrinsic disorder and folding upon binding have been integrated from specialized databases. The indirect evidence has also been expanded to better capture information available in the PDB, such as high temperature residues in X-ray structures and overall conformational diversity. Novel nuclear magnetic resonance chemical shift data provides an additional experimental information layer on conformational dynamics. Predictions have been expanded to provide new types of annotation on backbone rigidity, secondary structure preference and disordered binding regions. MobiDB 3.0 contains information for the complete UniProt protein set and synchronization has been improved by covering all UniParc sequences. An advanced search function allows the creation of a wide array of custom-made datasets for download and further analysis. A large amount of information and cross-links to more specialized databases are intended to make MobiDB the central resource for the scientific community working on protein intrinsic disorder and mobility.